Analisis Kebutuhan dan Penataan Ruang Parkir Kendaraan Roda Dua (2) di Museum Peta Kota Blitar - Benediktus Ogan, Ari; Primasworo, Rifky Aldila; Pandulu, Galih Damar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
The Peta Monument in Blitar was built to commemorate the PETA (Defenders of the Fatherland) rebellion against the Japanese army on February 14, 1945 led by Soedanco Soepriyadi. The Peta monument is located on Jl. Sudanco Supriyadi, Bendogerit, Sananwetan sub-district, Blitar city, East Java 66133. The existence of the PETA Army Headquarters Area as one of Blitar City's cultural heritage assets. The main problem identified is that the parking lot has not been optimally utilized, there is no good and ideal parking plot marking as a parking area, especially for two-wheeled vehicles and four-wheeled vehicles and other vehicles visiting the Map Monument. An adequate parking lot is able to meet the capacity of the parking lot so that it can satisfy visitors visiting the Blitar Map Monument. The purpose of this study is to determine the prediction of vehicle parking, parking capacity, and parking space arrangement. The data used are primary data and secondary data. Where the results of the research of two-wheeled vehicle parking needs are 35 SRP, four-wheeled vehicles are 104 SRP and bus parking is 5 SRP. Therefore, parking arrangements are made to obtain the availability of parking for two-wheeled vehicles (motorbikes) 163 SRP with a parking angle of 90°, four-wheeled vehicles (cars) 104 SRP with a parking angle of 45°, and bus parking 5 SRP with a parking angle of 90°.